Geographic social vulnerability is associated with the alpha diversity of the human microbiome - Nicole Farmer; Katherine A. Maki; Jennifer J. Barb; Kelly K. Jones; Li Yang; Yvonne Baumer; Tiffany M. Powell-Wiley; Gwenyth R. Wallen (mSystems, 2023)
ABSTRACT The human microbiome ecosystems living within the human body are exposed to exogenous foreign substances from the various environments that humans live within. Therefore, dynamics between microbes and human hosts can be influenced by environmental changes, which potentially impact microbiome composition and diversity. Geographic area, as a microbiome-relevant environmental factor, has been well reported. Human geography, however, is often linked to socioeconomic status, racial and ethnic population enclaves, and disparities in area disadvantage. Potential mechanisms linking the microbiome to factors tied to area disadvantage include household crowding, use of public transportation, and lack of exposure to biodiverse natural environments. Through an analysis of data from the Human Microbiome Project including healthy adults who reported residential area information at the time of microbiome sampling (n = 201), we found a significant relationship between the social vulnerability index (SVI), as a measure of area disadvantage, and multiple alpha diversity measures across oral, airways, and urogenital sites when controlling for age, gender, and body mass index. With regard to race/ethnicity, we found significant mediation by SVI score to explain racial/ethnic differences in urogenital microbiome diversity in females. Our results highlight the importance of considering environmental variables such as area social vulnerability as a variable of interest in microbiome studies within healthy individuals and suggest a potential role to explain urogenital race/ethnicity differences. Future studies including a diverse, representative community-based population, more precise residential location, and inclusion of related risk factors such as dietary intake, are needed to further understand the implications of these results. IMPORTANCE As a risk factor for conditions related to the microbiome, understanding the role of SVI on microbiome diversity may assist in identifying public health implications for microbiome research. Here we found, using a sub-sample of the Human Microbiome Project phase 1 cohort, that SVI was linked to microbiome diversity across body sites and that SVI may influence race/ethnicity-based differences in diversity. Our findings, build on the current knowledge regarding the role of human geography in microbiome research, suggest that measures of geographic social vulnerability be considered as additional contextual factors when exploring microbiome alpha diversity.